Control of Crystallinity in Nanocrystalline Silicon Prepared by High Working Pressure Plasma-Enhanced Chemical Vapor Deposition - Jung-Dae Kwon; Kee-Seok Nam; Yongsoo Jeong; Dong-Ho Kim; Sung-Gyu Park; Si-Young Choi (Advances in Materials Science and Engineering)
The crystalline volume of nanocrystalline silicon (Si) films could be successfully controlled simply by changing the substrate scan speed at the high working pressure of 300 Torr. The Si crystalline volume fraction was increased from 30% to 57% by increasing the scan speed from 8 to 30 mm/s. When the Si film was prepared at a low scan speed (8 mm/s), Si crystals of size 5 nm grew homogeneously through the whole film. The higher scan speed was found to accelerate crystallization, and crystals of size up to 25 nm were deposited in the Si film deposited when the scan speed was 30 mm/s.